PENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN MODEL SNOWBALL THROWING DAN MEDIA POHON KATA PADA SISWA KELAS VII E SMP NEGERI 16 SURAKARTA - Romadlon, Muhammad Rizqi; Suwandi, Sarwiji; Rakhmawati, Ani (Jurnal S2 Pendidikan Bahasa Indonesia, 2016)
This classroom action research aims to improve the quality of the learning process and improve the skills to write poetry at writing activity in class VII E SMP Negeri 16 Surakarta year 2015/2016. The results showed an increase in the quality of the learning process in the first cycle with the average value of the performance of teachers is 72 and the second cycle is 83, the average value of the performance of students in the first cycle and the second cycle is 70.85. Studentsâ kills in writing poetry is on increase, the studentsâ passing rate in the first cycle is 64 % with a mean value of 78 and the studentsâ passing rate in the second cycle is 92% with a mean value of 82. This is concluded that the implementation model of snowball throwing and said media tree can improve learning skills of writing poetry class VII E SMP Negeri 16 Surakarta academic year 2015/2016.